2022
DOI: 10.3390/bioengineering9120757
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Premolars with Four Canals: Case Series

Abstract: The aim of this case series is to contribute to the better knowledge and management of the complex anatomical configurations of maxillary premolars with four canals. The paper explains the endodontic treatment of five maxillary premolars with four canals, with three buccal and one palatal orifices, in different patients. The cases report several approaches in the treatment of four-canal maxillary premolars including a conservative canal preparation with a hybrid shaping technique, endodontic microsurgery and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Gender studies showed that root canal variation was 96.2% in men and 92.6% in women [ 5 ], and prevalence was 2.4% in men and 0.9% in women. Previous case reports show that three maxillary premolars have several root canals and root structures: three roots in one root, two in buccal roots, one in palatal roots, three separate roots and canal [ 13 15 ], and a rare four separate canal [ 16 18 ] in three premolars. This case report is aimed at reporting a rare case of maxillary first premolar three canals and their root canal therapy.…”
Section: Case Presentationmentioning
confidence: 99%
“…Gender studies showed that root canal variation was 96.2% in men and 92.6% in women [ 5 ], and prevalence was 2.4% in men and 0.9% in women. Previous case reports show that three maxillary premolars have several root canals and root structures: three roots in one root, two in buccal roots, one in palatal roots, three separate roots and canal [ 13 15 ], and a rare four separate canal [ 16 18 ] in three premolars. This case report is aimed at reporting a rare case of maxillary first premolar three canals and their root canal therapy.…”
Section: Case Presentationmentioning
confidence: 99%
“…Once bacteria arrive in the root pulp system, an endodontic treatment should be performed. The choice of endodontic treatment depends on the clinical situation [10].…”
Section: Root Canal Treatmentmentioning
confidence: 99%
“…Vital pulp therapy could be performed using pulp capping, partial pulpotomy, of full pulpotomy therapy [11][12][13]. Successful endodontic treatment consists of an appropriate access cavity [14], good shaping [15], proper cleaning using irrigants [16], and an optimal 3D obturation for the root canal system using sealer and gutta-percha [10,17,18]. Endodontic sealers must be used with gutta-percha to entomb the bacteria and ensure optimal sealing for the root canal system [19].…”
Section: Root Canal Treatmentmentioning
confidence: 99%